Active Power Filtering under Unbalanced and Distorted Grid Conditions Using Modular Fundamental Element Detection Technique - Hoon Y.; Zainuri M.A.A.M.; Al-Ogaili A.S.; Al-Masri A.N.; Teh J. (Institute of Electrical and Electronics Engineers Inc., 2023)
Active filters; MATLAB; Active power Filter; Active power filtering; Comparative analysis; Matlab-Simulink software; Overall control structure; Power system configuration; Three-phase three-wire; Time domain synchronous; Time domain analysis